The influence of divorce and other FOO factors on young-adult relationships - Kelly, Halldis M., author; Chavez, Ernest L., advisor; Bloom, Larry J., committee member; Loomis, Ross J., committee member; Banning, James H., committee member (Colorado State University. Libraries, 2001)
This study questions the proposition that children who experience their parents' divorce are predisposed to impairments in the formation of stable, long-lasting romantic unions in adulthood. The study investigates the contribution of family-of-origin (FOO) structure (divorced vs. intact FOO), FOO environmental characteristics (family rituals, positive family affect, family communication, family worries, family conflicts), and gender in predicting adult-children's relationship characteristics; very few divorce-related relationship studies have simultaneously considered these factors. Adult-children's relationship characteristics were assessed using measures of positive and negative relationship-communication strategies, relationship beliefs, and fear of intimacy. These factors have been associated empirically with the quality and stability of adult intimate relationships. Hierarchical regression analyses were used to simultaneously consider whether FOO structure, FOO environment, and gender would be predictive of adult-children's relationship characteristics. Results indicate that qualities of the FOO environment, rather than its structure, predict positive and negative relationship-communication strategies, relationship beliefs, and fear of intimacy in adult-children. Moreover, positive aspects of the FOO environment, rather than the presence or absence of negative FOO environmental characteristics, were most predictive of adult-children's relationship-communication, relationship beliefs, and fear of intimacy.
Keywords: social psychology